Practical Tips for Starting a Student-Run Free Eye Clinic [version 1; peer review: 1 approved, 2 approved with reservations] - Adam Leone; Robert Porter; Alec Murphy; Cameron Reinisch; Jonathan Regenold; Courtney Linne; Lisa Kelly; Hyun Jun Kim (MedEdPublish, 2024)
Student-run free clinics serve three primary functions: 1) providing basic medical services for the uninsured and underserved in our communities, 2) supporting the training of medical providers, and 3) advocating for medically underserved communities. Despite the multiple benefits that student-run free clinics can provide, the process of founding a clinic is a significant challenge, even for highly motivated students. Here, we present 12 tips generated by students and residents at the University of Cincinnati College of Medicine based on their combined experience in founding the Bearcat Eye Service (BES), a clinic that provides basic ophthalmic screenings. These tips were developed to provide a framework for those interested in founding a student-run free clinic or expanding ophthalmic care in their communities.